The Protective Effect of Magnolol in Osteoarthritis: In vitro and in vivo Studies - Hu, Zhi-Chao; Luo, Zu-Cheng; Jiang, Bing-Jie; Fu, Xin; Xuan, Jiang-Wei; Li, Xiao-Bin; Bian, Yu-Jie; Ni, Wen-Fei; Xue, Ji-Xin (Frontiers in Pharmacology, 2019)
Osteoarthritis (OA), defined as a long-term progressive joint disease, is characterized by cartilage impairment and erosion. In recent decades, magnolol, as a type of lignin extracted from Magnolia officinalis, has been proved to play a potent anti-inflammatory role in various diseases. The current research sought to examine the latent mechanism of magnolol and its protective role in alleviating the progress of OA in vivo as well as in vitro experimentations. In vitro, the over-production of Nitric oxide (NO), prostaglandin E2 (PGE2), cyclooxygenase-2 (COX-2), inducible nitric oxide synthase (iNOS), tumor necrosis factor alpha (TNF-α) and interleukin-6 (IL-6), induced by interleukin-1 beta (IL-1β), were all inhibited notably by magnolol in a concentration-dependent manner. Moreover, magnolol could also downregulate the expression of metalloproteinase 13 (MMP13) and thrombospondin motifs 5 (ADAMTS5). All these changes ultimately led to the deterioration of the extracellular matrix (ECM) induced by IL-1β. Mechanistically, magnolol suppressed the activation of PI3K/Akt/NF-κB pathway. Furthermore, a powerful binding capacity between magnolol and PI3K was also revealed in our molecular docking research. In addition, magnolol-induced protective effects in OA development were also detected in a mouse model. In summary, this research suggested that magnolol possessed a new therapeutic potential for the development of OA.